The IL-10/STAT3 Axis Nasopharyngeal Carcinoma Cancer stem cell and radio resistance - Li-jun Wang; Ying Zhao; Yan-sheng Wang; Lei Xing; Yun-jing Duan; Huan-huan Zang (Scientific Reports)
Abstract One of the primary reasons for the failure of therapy in nasopharyngeal cancer (NPC) is radio resistance-related localized one, which may lead to tumor residuals or recurrences. Several studies have linked interleukin-10 (IL-10) to crucial functions in cancer development and response to therapy. Its function in NPC’s radio resistance is, however, not well understood. Enzyme-linked immunosorbent assay (ELISA) and quantitative real-time PCR were utilized for confirming IL-10 expression in NPC cell lines. The prognostic significance of IL-10 was also assessed via Kaplan-Meier analysis. CNE2R, a radioresistant NPC cell line, expressed IL-10 at high levels, which were also shown to be considerably elevated in individuals with radioresistant NPC, as measured by ELISA. Moreover, the levels were also linked to poor clinical outcomes and prognosis in cancer cases. We also showed some evidence of a link between hypoxia-inducible factor 1-alpha (HIF-1 A) and serum IL-10 levels in NPC. Meanwhile, we find that IL-10 is up-regulated in CSC. IL-10 enhanced the self-renewal and tumorigenesis of nasopharyngeal CSC. In terms of mechanism, IL-10 enhances nasopharyngeal CSC self-renewal and tumorigenesis by activating STAT3 pathway. In NPC, IL-10/STAT3 Axis Nasopharyngeal Carcinoma Cancer stem cell and radio resistance.